Determination of Segmentation Based H.264/AVC Using Octagon and Square Search Pattern in Adaptive Group of Pictures Mode - S. Sowmyayani; V. Murugan (New Approaches in Engineering Research Vol. 13, 2021)
A Video occupies more space than images. There are several video compression technologies which yield low data rate for faithful transmission and reproduction of videos. If the video is compressed, it occupies less space. Also, size of the video has an impact on transmission in video conferencing and other broadcasting applications. One among several video compression standards is H.264/AVC. This chapter modifies the architecture of H.264/AVC and develops a framework for video compression.